Kontribusi Industri Gula Aren terhadap Pendapatan Rumah Tangga Petani di Desa Belimbing, Kecamatan Pupuan, Kabupaten Tabanan - SUSANNA E.R. SIMAMORA; I WAYAN WIDYANTARA; NI WAYAN PUTU ARTINI (Agribusiness Study Program, Faculty of Agriculture, Udayana University, 2020)
Contributions of Palm Sugar Industryon Farmers Household Incomein Belimbing Village, Pupuan Sub-District, Tabanan Regency The palm sugar industry is one of the side livelihoods for most people in BelimbingVillage. Belimbing Village is one of the villages in the Province of Bali that has beendesignated as the center of NIKOSAKE (Nira (palm sugar), Kopi (Coffee), Salak(Snake fruit), Kelapa (Coconut). This study aims to find out: 1) Sources of income offarmer households in Belimbing Village. 2) Contribution of palm sugar industry to theincome of farmer households in Belimbing Village. The data analysis method used isquantitative and qualitative methods. This study shows that the source of income offarmer households in Belimbing Village, Pupuan Subdistrict, Tabanan Regency comesfrom palm sugar industry, farming (rice, coffee, durian, mangosteen, coconut, cocoa,bamboo, and banana), and non-farming ( traders and laborers). The results obtained, theaverage household income of palm sugar is Rp 5,062,162 per year, the average farmincome is Rp 12,053,359 per year, and the average non-farm income is Rp 10,156,441per year.